A conceptual framework for studying the effects of cross-cultural training, expatriates' personality, self-efficacy, and social network composition on adjustment and performance in overseas assignments - Gani, Aahad M. Osman (Higher Education Press, 2008)
This paper presents a conceptual framework for conducting empirical investigations to study the effects of cross-cultural training, expatriates' personality, self-efficacy, and social network compositions on their adjustments and performance in overseas assignments. Developed based on extensive reviews of literature, and findings from prior research, the framework would be useful in developing relevant research agenda. This paper concludes by proposing some research hypotheses that would provide specific guidance for conducting empirical research in future.